1989
DOI: 10.1115/1.3188744
|View full text |Cite
|
Sign up to set email alerts
|

In-Process Detection of Tool Failure in Milling Using Cutting Force Models

Abstract: The authors show that first and second differencing of a time averaged resultant force is extremely effective in the recognition of tool breakage in milling. In order to be useful in production, however, such a system needs to have a knowledge of allowable levels of the first difference. It is shown that these levels, (thresholds), are extremely dependent on the ratio of cutter radius to width of cut, (immersion ratio). A method of on-line identification of the immersion ratio and threshold tuning is presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
2

Year Published

1995
1995
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(61 citation statements)
references
References 0 publications
1
58
0
2
Order By: Relevance
“…Although the indirect methods, particularly those based on acoustic emission [6,5,25,23], are quite promising, more research is needed before they can be widely implemented. The cutting-forcebased methods have, on the other hand, more solid theoretical background, and therefore they are more attractive for modeling the metal-cutting processes [3,19,20,7,22,27,17]. It is interesting to note that a combined approach, incorporating an 'intelligent sensor', becomes a new paradigm in metal-cutting-process control [26,31].…”
Section: Metal-cutting-process Space and Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the indirect methods, particularly those based on acoustic emission [6,5,25,23], are quite promising, more research is needed before they can be widely implemented. The cutting-forcebased methods have, on the other hand, more solid theoretical background, and therefore they are more attractive for modeling the metal-cutting processes [3,19,20,7,22,27,17]. It is interesting to note that a combined approach, incorporating an 'intelligent sensor', becomes a new paradigm in metal-cutting-process control [26,31].…”
Section: Metal-cutting-process Space and Sensorsmentioning
confidence: 99%
“…The measurements are taken at times of the tool rotation incremented by one degree When all cutting edges of the tool are sharp, the cutting force is periodic, with approximately the same frequency. If, however, one of the teeth is worn, then the force amplitude for this tooth, and perhaps for the following teeth, is disturbed [3]. The following force model was used for the case when the first tooth is worn:…”
Section: Ntmentioning
confidence: 99%
“…For example, Altintas [2] has shown that the first-order autoregressive time series model AR1 can be used to distinguish the force signal during normal flank wear to that when tool failure occurs. Elbestawi et al [3] found that certain harmonics of the cutting force increase significantly with flank wear, the number of such sensitive harmonics being related to the number of inserts of the milling cutter and the immersion rate.…”
Section: Kious Is With Semiconductor and Functional Materials Labomentioning
confidence: 99%
“…In most approaches, proposed for the tool wear monitoring area, several parameters can be measured, such as forces, vibrations and acoustic emission, which are directly correlated with tool wear [3]- [7]. Furthermore, these parameters are measured on-line during the machining process.…”
Section: Introductionmentioning
confidence: 99%
“…A frequent approach used in laboratories is to attach vibration, acoustic emission and dynamometer sensors to the machine and then monitor the signals obtained. The measurement of cutting force is commonly taken using a table-mounted dynamometer, which is an essential tool for laboratory based experimental work [4][5][6]. Flank wear and tooth breakage can be monitored from acceleration and vibration signals during milling [7,8].…”
Section: Introductionmentioning
confidence: 99%